The voyages of Doctor Dolittle - Lofting, Hugh, 1886-1947 (Books of wonder., 2001)
When his colleague Long Arrow disappears, Dr. Dolittle sets off with his assistant, Tommy Stubbins, his dog, Jip, and Polynesia the parrot on an adventurous voyage over tropical seas to floating Spidermonkey Island.